PENGELOLAAN SUMBERDAYA ALAM TERBARUKAN, Study Kasus: Penelitian Pendahuluan Produksi Gula dan Bioethanol dari Tumbuhan Nipa (Nipa frutican) di Bagansiapi-api Rohil (Jurnal Kajian Lingkungan, 2014)
Experimental of preliminary study was conducted to know production of sugar and theirethanol content from Nipafruticanin the Stasiun Riset BioetanolMangrove Nipa ofBagan Siapi-api Rokan Hilir, Riau, from February to Marc 2010. Production of Nipaâssugar was increased by 6 days of experiment, and from that time (6 days) showed a fewflucuation till the 14 days of experiment. No significant effect of nira productionbetween twohands andthree hands fruitof each Nipaclump which isextracted theirsugar.Sugar of Nipafrutican contained between 18 to 24 brix, and could produced about1 liter (99,64%) ethanol from 7 liters of its sugar.The peopleâs involvement in efforts toextract sugar of Nipa for producing sugar and bioethanol could become one of a strategyin a sustainable management of mangrove ecosystem(Nipa).